Correction: Carbon nanotube-copper exhibiting metal-like thermal conductivity and silicon-like thermal expansion for efficient cooling of electronics. Issue 4 (15th January 2019) - Subramaniam, Chandramouli; Yasuda, Yuzuri; Takeya, Satoshi; Ata, Seisuke; Nishizawa, Ayumi; Futaba, Don; Yamada, Takeo; Hata, Kenji
Abstract : Correction for 'Carbon nanotube-copper exhibiting metal-like thermal conductivity and silicon-like thermal expansion for efficient cooling of electronics' by Chandramouli Subramaniam and Kenji Hata et al., Nanoscale, 2014, 6, 2669–2674.